Pre‐Metastatic Niche: Biomaterial Scaffolds as Pre‐metastatic Niche Mimics Systemically Alter the Primary Tumor and Tumor Microenvironment (Adv. Healthcare Mater. 10/2018). Issue 10 (May 2018) - Aguado, Brian A.; Hartfield, Rachel M.; Bushnell, Grace G.; Decker, Joseph T.; Azarin, Samira M.; Nanavati, Dhaval; Schipma, Matthew J.; Rao, Shreyas S.; Oakes, Robert S.; Zhang, Yining; Jeruss, Jacqueline S.; Shea, Lonnie D.
Abstract : Biomaterial implants that mimic the premetastatic niche are shown to redirect immune and tumor cell populations in vivo. However, the systemic effects of premetastatic niche mimics on metastasis progression have yet to be characterized. In article1700903 by Lonnie D. Shea and co‐workers, synthetic biomaterial implants are shown to systemically alter the primary tumor and the tumor microenvironment to promote an invasion‐suppressive phenotype. Cover art designed and produced by Stephen Alvey, University of Michigan, Department of Engineering.